Kode Vicious unscripted. - Neville-Neil, George (ACM queue : architecting tomorrow's computing., 2005)
Some months, when he's feeling ambitious, Kode Vicious reads through all of your letters carefully, agonizing for days over which to respond to. Most of the time, though, he takes a less measured approach. This usually involves printing the letters out, throwing them up in the air, and seeing which land face up, repeating the process until only two remain. And occasionally, KV dispenses with reader feedback altogether, as is the case this month. Not to worry though, he still digs reading and responding to your monthly koding kwestions, so keep 'em coming to kv@acmqueue.com.